Myosin Heavy Chain Composition of the Human Hyoglossus Muscle - Sokoloff, Alan J. (2009)
The human tongue muscle hyoglossus (HG) muscle is active in oro-motor behaviors encompassing a wide range of tongue movement speeds. Here we test the hypothesis that the human HG is composed of “uncommon” myosin heavy chain (MHC) isoforms MHCembryonic, MHCneonatal and MHCslow tonic as has been reported for other head and neck muscles active during kinematically diverse behaviors. Following reaction of human HG with antibodies specific for MHCI, MHCIIA, MHCII, MHCembryonic, MHCextraocular, MHCneonatal and MHCslow tonic only antibodies to MHCI, MHCIIA and MHCIIA-X label more than occasional muscle fibers. These antibodies describe five phenotypes with prevalence MHCIIA>MHCI>MHCI-IIX>MHCI-IIA>MHCIIX. In MHC composition, the human HG is thus similar to human appendicular muscles, the human tongue muscle styloglossus and many human head and neck muscles but different from human masseter and extraocular muscles which contain five or more MHC isoforms.